Understanding students' future intention to engage in sustainability accounting: the case of Malaysia and the Philippines - Eugénio, T.; Carreira, P.; Miettinen, N.; Lourenço, I. (Journal of Accounting in Emerging Economies, 2022)
Purpose: The study investigates whether the level of sustainability concerns of Higher Education Institutions (HEIs) in Malaysia and the Philippines is positively associated with accounting students' intentions to engage in sustainability accounting through its effect on students' attitude, subjective norm and perceived behavioural control regarding environmental sustainability practices. Design/methodology/approach: This empirical study relies on a structural equation model computed using data collected through a questionnaire and data collected from the HEIs websites. Findings: The findings show that the willingness to engage in sustainability accounting is determined by students' subjective norm and perceived behavioural control, but it is not determined by attitude regarding environmental sustainability practices. The authors also found that the greater the concern with sustainability of the HEI in which a student is enrolled, the greater his/her attitude, subjective norm and perceived behavioural control towards environmental sustainability, and, indirectly, the greater his/her intention to engage in sustainability accounting. Originality/value: These findings add to the literature on higher education and sustainability accounting by high-lighting the importance of the HEIs sector in promoting sustainability policies and practices, in acting as role models regarding sustainability issues, and in preparing students for building a sustainable society.